A numerical study on the optimal placement of two air purifiers for simultaneous operation in a school classroom - Chengxi Yao; Seungjae Lee; Taesung Kim (International Journal of Air-Conditioning and Refrigeration)
Abstract In educational environments such as school classrooms, indoor air quality has a significant impact on the health and learning ability of children and adolescents. This study investigates how to optimally place and operate two air purifiers in a national standard-size classroom to improve air quality uniformly and effectively. Ten cases were analyzed using computational fluid dynamics (CFD) simulations, considering various placements and airflow directions of air purifiers. The air purification performance was evaluated by monitoring changes in the concentrations of major pollutants in the classroom, including PM2.5 and CO2, and the airflow distribution and average air age index were applied to evaluate the airflow circulation. The results showed that when the air purifiers were placed symmetrically to minimize mutual discharge airflow interference, pollutant removal and airflow uniformity were maximized. Case 3, where the air purifiers were placed at opposite corners of the classroom to circulate air throughout the classroom, showed the best performance. This study provides a systematic approach and analysis results to optimize indoor air quality in classrooms and contribute to student health and learning environments.